Noninvasive Molecular Imaging of Disease Activity in Atherosclerosis. Issue 2 (8th July 2016) - Dweck, Marc R.; Aikawa, Elena; Newby, David E.; Tarkin, Jason M.; Rudd, James H.F.; Narula, Jagat; Fayad, Zahi A.
Abstract : Major focus has been placed on the identification of vulnerable plaques as a means of improving the prediction of myocardial infarction. However, this strategy has recently been questioned on the basis that the majority of these individual coronary lesions do not in fact go on to cause clinical events. Attention is, therefore, shifting to alternative imaging modalities that might provide a more complete pan-coronary assessment of the atherosclerotic disease process. These include markers of disease activity with the potential to discriminate between patients with stable burnt-out disease that is no longer metabolically active and those with active atheroma, faster disease progression, and increased risk of infarction. This review will examine how novel molecular imaging approaches can provide such assessments, focusing on inflammation and microcalcification activity, the importance of these processes to coronary atherosclerosis, and the advantages and challenges posed by these techniques.